Culture and violence against LGBTQ+ persons: International contexts and issues in contemporary societies - Moleiro, C.; Solntseva, S.; Aybar, G. (Violence against LGBTQ+ persons: Research, practice, and advocacy, 2021)
Culture has been increasingly recognized as being central to human experience and in understanding intergroup relations, power, social identities and interpersonal interactions in everyday life in diverse societies, with distinct legal, religious, family and social systems. This chapter is grounded on the recognition that discrimination and violence against LGBTQ+ persons are best understood in a cultural context, as culture shapes attitudes toward gender, sexual orientation and gender identities and expressions. It examines the role of culture in shaping violence against LGBTQ+ persons internationally, as well as the literature on LGBTQ+ migrants, refugees and asylum seekers in contemporary societies. It also presents a case illustration of Chechen queer people and multi-dimensional levels of violence. The chapter ends with reference to the facilitation of healing and resilience among LGBTQ+ survivors of violence in international contexts.